Glucose-activatable insulin delivery with charge-conversional polyelectrolyte multilayers for diabetes care - Yang, Yanguang; Wang, Xiangqian; Yuan, Xiaopeng; Zhu, Qiwei; Chen, Shusen; Xia, Donglin (Frontiers in Bioengineering and Biotechnology, 2022)
One of the most effective treatments for diabetes is to design a glucose-regulated insulin (INS) delivery system that could adjust the INS release time and rate to reduce diabetes-related complications. Here, mixed multiple layer-by-layer (mmLbL)-INS microspheres were developed for glucose-mediated INS release and an enhanced hypoglycemic effect for diabetes care. To achieve ultrafast glucose-activated INS release, glucose oxidase (GOx) was assembled with a positively charged polymer and modified on INS LbL. The mmLbL-INS microspheres were constructed with one, two, and four layers of the polyelectrolyte LbL assembly at a ratio of 1:1:1. Under hyperglycemia, GOx converts a change in the hyperglycemic environment to a pH stimulus, thus providing sufficient hydrogen ion. The accumulated hydrogen ion starts LbL charge shifting, and anionic polymers are converted to cationic polymers through hydrolytic cleavage of amine-functionalized side chains. The results of in vitro INS release suggested that glucose can modulate the mmLbL-INS microspheres in a pulsatile profile. In vivo studies validated that this formulation enhanced the hypoglycemic effect in STZ-induced diabetic rats within 2 h of subcutaneous administration and facilitated stabilization of blood glucose levels for up to 2 days. This glucose-activatable LbL microsphere system could serve as a powerful tool for constructing a precisely controlled release system.